1986
DOI: 10.1073/pnas.83.15.5494
|View full text |Cite
|
Sign up to set email alerts
|

Isolated liver gap junctions: gating of transjunctional currents is similar to that in intact pairs of rat hepatocytes.

Abstract: We have shown previously that conductance of rat liver gap junctions is blocked by an affinity-purifiled

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 17 publications
3
32
0
Order By: Relevance
“…Channels composed of pGF5 have a measured unitary conductance value of 160 pS. This is of interest because the length of the pGF5 cytoplasmic tail domain approximates that of the wild-type connexin32 protein, whose channels have a similar unitary conductance, as determined in several cell types and expression systems, including acinar cells (20), isolated liver junctional membranes incorporated into lipid bilayers (21,22), and SKHepl cells transfected with connexin32 cDNA (10).…”
Section: Discussionmentioning
confidence: 99%
“…Channels composed of pGF5 have a measured unitary conductance value of 160 pS. This is of interest because the length of the pGF5 cytoplasmic tail domain approximates that of the wild-type connexin32 protein, whose channels have a similar unitary conductance, as determined in several cell types and expression systems, including acinar cells (20), isolated liver junctional membranes incorporated into lipid bilayers (21,22), and SKHepl cells transfected with connexin32 cDNA (10).…”
Section: Discussionmentioning
confidence: 99%
“…voltage (Bennett and Verselis, 1992;Spray et al, 1986), growth factors (Lau et aI., 1992;Madhukar et aI., 1989;Maldonado et aI., 1988), and transforming oncogene activity (Atkinson and Sheridan, 1985;Azarnia et al, 1988). The mechanisms which mediate changes in gap junctional permeability are at present incompletely understood.…”
Section: 1)mentioning
confidence: 99%
“…Functional demonstration that a given polypeptide is capable of forming an intercellular channel should be obtained by showing that dye and/or electrical coupling between two adjacent cells is/are blocked after intracellular micro-injection of specific antibodies against the candidate protein [40,41]. In addition, reconstitution of the purified protein into lipid bilayers should allow for a direct functional assessment of the electrophysiological properties of the putative channel the protein may form [42,43]. Another elegant approach, which has already been applied successfully, involves the introduction of the specific mRNA coding for a gap junctional protein into cells, followed by the measurement of the ability of these cells to communicate [44].…”
Section: Molecular Structure Of the Gap Junctional Channelmentioning
confidence: 99%
“…The presence of extensive coupling within an acinus raises the obvious question of its role under resting conditions and makes it likely that relevant information could be gathered by modulating the extent of cell-to-cell communication. As a first approach to this modulation, we have used alcohols such as heptanol, octanol and nonanol, which have been shown to block synaptic transmission and cell coupling [63,64] by a still undetermined mechanism that may involve their direct interaction with gap junctions [42]. We found that heptanol causes a marked reduction of the dye [I 1,121 and electrical [65] coupling within intact pancreatic acini, and abolishes, within seconds, the conductance of junctional channels between pairs of acinar cells [65].…”
Section: The Exocrine Pancreasmentioning
confidence: 99%